IMPLEMENTASI PROGRAM KETERAMPILAN VOKASIONAL BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH MENENGAH PERTAMA - KHOTIMAH, KHUSNUL; , SUJARWANTO (Jurnal Pendidikan Khusus, 2019)
ABSTRACT Vocational skills for special needs students had the functions to improve their ability to work according to their talents and interests so that they will be able to work and create jobs for themselves later, also to enhance entrepreneurial spirit, work spirit, and being beneficial for the community. The purpose of this study was to describe the implementation of vocational skills program for special needs students in state junior high school 1 sidorejo magetan. The obstacles on the implementation of vocational skills programs, as well as solutions to overcome in the implementation of vocational skill?s programs in state junior high school 1 sidorejo magetan. This study used a qualitative approach with a type of qualitative descriptive research self report. Data were collected through: interviews, observation, and documentation. Then, data were analyzed by the Miles, Huberman, & Saldana analysis models (2014: 14) which included: data condensation, data presentation, and verification and conclusion. The results showed that the types of skills carried out in state junior high school 1 sidorejo magetan included cooking, drawing, gardening, handy craft (making flowers from used plastic), electrical engineering (making simple garden lights) and making simple waterwheels. The implementation of vocational skills was in line with the steps that exist even though there are some discrepancies in terms of implementation in the field. For example, the implementation of vocational skills that were not according to the schedule that had been made, there was no guidelines for the implementation of vocational skills program, there was no evaluation instruments, and there was no follow-up related to the actions which were taken after vocational skills were mastered by special needs students. Moreover, the obstacles in the implementation of vocational skills i.e.,: lack of infrastructure, limited time for teachers developing vocational skills, students for several reasons do not want to take part in the activity. Solutions that have been done by the teacher to overcome the existed obstacles i.e.,: using the available equipment, bringing equipment from home, changing the schedule of implementation skills program, and advising and motivating Keywords : vocational skills, special needs students, junior high school